Income Differences of Sago Processing Farmers and Upland Rice Farmers in Southeast Sulawesi Province - Surni, Surni; Zani, Munirwan; Yunus, Lukman (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
This research is motivated by the need for food for the local community of Southeast Sulawesi Province. Food diversification by preserving local food, sago, and brown rice from upland rice. Foodstuffs that are handled differently are first handled in groups for sago and done by farmers and their families for upland rice. The study aimed to analyze the differences in income between sago processing farmers and upland rice farmers. The research was conducted in two locations, namely: (1) sago processing group in Lameuru Village, West Ranomeeto District, South Konawe Regency, and (2) upland rice farmers in Bubu Village, Kambowa District, North Buton Regency. Determination of research locations by purposive for as many as ten people for sago processors. By Simple Random Sampling for upland rice farmers as many as 24 people. The analytical tool used is descriptive analysis with a t-test. According to the findings, sago processors' average monthly income was IDR1,791,400.00, more than Indonesian farmers' average monthly income of IDR1,600,000 in 2016. Upland rice farmers earn an average of IDR1,116,726.20 per month, more than the IDR1,000,000.00 per month average for Indonesian farmers in 2017. The results of the t-test showed a significant difference between the income of sago processors and the average income of upland rice farmers.